2021
DOI: 10.1016/j.sjbs.2021.01.019
|View full text |Cite
|
Sign up to set email alerts
|

A study on risk assessment of effect of hematoxylin dye on cytotoxicity and nephrotoxicity in freshwater fish: Food and water security prospective research

Abstract: The cytotoxicity in freshwater fishes due to different industrial dyes in industrial effluents is a major worldwide issue. Hematoxylin dye has a wide range of uses in textile industries and laboratories. This study was aimed to evaluate the toxic effects of hematoxylin's sublethal effect in vitro in Cirrhinus mrigala . The fish was exposed to different grading concentrations of dye in the aquarium. Fish were sacrificed and dissected to remove the kidney after exposure to hematoxylin dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…In a recent in vitro study, hematoxylin dye showed several changes in the kidney (glomerulonephritis, tubular degeneration, etc.) of a fish Cirrhinus mrigala [46]. Previous studies on Gambusia affinis have demonstrated significant cytotoxic effects on RBCs.…”
Section: Impact Of Dyes On Fishmentioning
confidence: 90%
See 1 more Smart Citation
“…In a recent in vitro study, hematoxylin dye showed several changes in the kidney (glomerulonephritis, tubular degeneration, etc.) of a fish Cirrhinus mrigala [46]. Previous studies on Gambusia affinis have demonstrated significant cytotoxic effects on RBCs.…”
Section: Impact Of Dyes On Fishmentioning
confidence: 90%
“…Fish suffer from a variety of physiological and biochemical abnormalities as a result of changes in water quality [45]. Fish are vulnerable to a wide variety of toxins including dyes from industrial effluents [46]. Dyes regularly come into close contact with fish during respiration through gills.…”
Section: Impact Of Dyes On Fishmentioning
confidence: 99%
“…Na maior dose de estudo (0,018 mg/L) observou-se redução significativa no crescimento, perda de peso dos peixes e danos renais severos como aumento do espaço tubular, entupimento e degeneração dos túbulos e necrose renal, esses resultados estão associados a interferência do corante hematoxilina no processo de filtração dos rins dos peixes os levando a problemas severos que afetam o seu desenvolvimento. Diante disso, fica constatado que este corante mesmo em baixa concentração nos corpos d'água causam bastante efeitos tóxicos para a fauna aquática (HUSSAIN et al, 2021).…”
Section: Efeitos Ecotoxicológicos Aquáticos Dos Corantes Têxteisunclassified
“…Exposure to hematein through ingestion or close contact may cause eye damage, respiratory and skin irritation, and pose a risk if swallowed. Repeated or prolonged exposure can even result in organ failure. In a study by Hussain et al, the impact of hematein (hematoxylin) on nephrotoxicity and cytotoxicity in freshwater fish was assessed, revealing that the discharged dye in wastewater is highly toxic to living organisms, particularly aquatic fauna, even at low concentrations. The safety data sheet for hematein recommends disposal in a closed container, offering limited guidance on subsequent treatment.…”
Section: Introductionmentioning
confidence: 99%